A case study on conflict intensity between humans and elephants at Teknaf Wildlife Sanctuary, Cox’s Bazar, Bangladesh - Hossen, Amir; Røskaft, Eivin (Frontiers in Conservation Science, 2023)
Humans and elephants’ conflict is considered a common phenomenon in Bangladesh due to extreme anthropogenic interferences on elephant habitats. Concurrently, the landless people were encouraged to encroach on forest land due to their financial hardship and poor and weak forest management system. We conducted our research work through frequent field visits, site-oriented positioned research correspondents as well as an adopted semi-structured questionnaire. We recorded a total number of 903 conflict related cases between humans and elephants including crop raids (N = 337), house raids (N = 200), homestead garden raids (N = 263), and accidental attacks (N = 103), across sites, during August 2018 to July 2019, in Teknaf Wildlife Sanctuary (TWS). Elephant attack rates varied significantly between traditional forest dwellers (N = 179), illegal settlers (N = 370), villagers nearest forest (N = 212), Rohingya refugees (N = 53), and traditional forest different tribes (N= 89). It also varied along a space gradient including inside forests (N = 423), buffer zones (N = 297), and outside forest villages (N = 183). The number of conflicts possessed by elephants varied discriminately and unparalleled among different professions as cattle ranchers (N = 104), gardeners (N = 112), paddy cultivators (N = 236), vegetable growers (N = 158), betel-leaf growers (N = 163), and forest resources collectors (N = 130), Most conflicts between humans and elephants occurred significantly during the night (N = 592), many during the morning (N = 154), evening (N = 138), and much less during midday (N = 19). The conflict intensity also inclined on the east coast (N = 552), and more than on the west coast (N = 351). The seasonal variation including summer (N = 367), monsoon (N = 274), and winter (N = 262) was also significant. The elephant herd size was also an important factor triggering the conflict in TWS. We conclude that conflict intensity between humans and elephants is driven by settlers’ location, forest gradient, the profession of forest dependent people, their household size and income level, attack time, and season.